A comparative study between the performance of 4th and 6th grade students in solving Sequence of Patterns tasks - Santana, Rita de Cássia Calazans Lemos; Magina, Sandra (Educação Matemática Debate, 2025)
This paper aims to investigate and compare the performance of 4th and 6th grade students in solving tasks involving Sequence Patterns of the Crescent and Repetitive types, in the iconic and numerical contexts, using qualitative and quantitative methodological approaches. The study involved 81 students who solved four sequence pattern tasks. The analysis was based on relevant theories and test statistics. The results showed that 6th graders got 68% right, while 4th graders got 47%. Despite this difference, the statistical analysis did not consider it significant. This study highlights the relevance of research to understanding algebra performance in the early years of primary school, suggesting new areas for investigation.